Makna Slogan ”Al-Aqsa Haqquna” Pada Aksi Bulan Solidaritas Palestina - Arif Ramdan Sulaeman; Fuad Buntoro (Jurnal Komunikasi dan Media, 2024)
The slogan ‘Al-Aqsa Haqquna’ which means ‘Al-Aqsa Mosque belongs to us’ has become a symbol of struggle in the solidarity campaign for Palestine. Introduced by the Aqsa Working Group (AWG) since 2006, the slogan asserts the right of Muslims to Al-Aqsa Mosque under Israeli occupation. In this study, Roland Barthes' semiotic theory is used to analyse the meaning of the slogan in various forms, such as chants in solidarity rallies and visual media such as posters.This study uses qualitative and quantitative methods, with descriptive analysis techniques to illustrate how this slogan shapes the collective consciousness of Muslims. The meaning of ‘Haqquna’ (our right) in this slogan reflects absolute ownership that cannot be taken away, emphasising the urgency of the struggle for the liberation of Al-Aqsa.The results show that this slogan is not only a unifier in solidarity actions, but also strengthens the identity of the struggle for the Palestinian people. The sound of this slogan in various countries, including Indonesia, builds the spirit of togetherness and provides moral support for the Palestinians. As a recommendation, this slogan should be patented as an intellectual right and designed in a uniform typography and colour to make it easier to identify. This research is useful for humanitarian organisations and Muslim movements in strengthening solidarity communication strategies for Palestine.